A prospective study to assess the prevalence of hepatitis B infection in health care workers, voluntary blood donors, and patients with liver disorders at a tertiary care centre - Kaundal, Purshottam K.; Kaundal, Anju Partap (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hepatitis B virus (HBV) is highly infectious when compared with human immuno-deficiency virus (HIV), even minute quantity of infected blood as little as 0.0001 ml can transmit infection. A number of the routine therapeutic, diagnostic, prophylactic invasive procedures can spread HBV infection. The study was planned to assess the prevalence of hepatitis B surface antigen in health care workers, voluntary blood donors, and patients with liver disorders. Methods: The study was a cross sectional study carried out among 90 subjects during a period of one year in Indira Gandhi Medical College and Hospital, Shimla. These 90 subjects consisted of 30 patients with liver disorder, 30 health care workers and 30 voluntary blood donors. The blood samples were collected and sent for detection of HBsAg by ELISA. Results: Majority of the subjects 47 (52.2%) belonged to the age group of 21-30 years. Among voluntary blood donors, 90% were males. 64.4% of the subjects belonged to urban areas. 50% of the rural subjects were having liver disorders. Liver disorder was more common (71.5%) among heterosexual high risk behaviour subjects compared to only 25.7% with no high risk behaviour. Seropositivity was found highest among patients with liver disorder (66.7%) followed by health care workers (20%). Overall, the seropositivity was 28.9%. Conclusions: Patients with liver disorders especially chronic hepatitis were mostly seropositive. Among health care workers, being a doctor was a significant risk factor for acquiring hepatitis B infection. Thus, it is advised that all health care workers should be immunized for hepatitis B.